Progress of the Target Selection and Localization of Repetitive Transcranial Magnetic Stimulation to Improve Upper Limb Function after Stroke - LIU Canhuan; SHEN Ying; DAI Wenjun; GUO Chuan; CHENG Yihui; ZHU Yi; WANG Tong (康复学报)
Stroke is a common cerebrovascular disease with high morbidity, mortality, disability, and recurrence imposing significant social and economic burdens. Following a stroke, approximately 30%-60% of patients experience varying degrees of upper limb motor dysfunction. Currently, rehabilitation techniques for improving post-stroke upper limb motor function, both domestically and internationally, primarily involve motor function training.Repetitive transcranial magnetic stimulation (rTMS), because it can enhance upper limb motor function recovery by modulating cortical excitability and promoting neuroplasticity, has been increasingly used in stroke rehabilitation and has been included in the guideline as a grade A recommendation.However, there is still large heterogeneity in the relevant clinical studies, and the therapeutic effect is affected by factors such as different target selection and target localization accuracy. In recent years, the number of studies on new stimulation targets and different localization methods has been increasing. In this paper, we review the protocols, efficacy, mechanism of action, and localization of stimulation targets of rTMS in the primary motor cortex (MI), premotor cortex (PMC), and other brain regions, aiming to provide guidance for the clinical application of rTMS in the rehabilitation of upper limb motor function after stroke.